PENGARUH KAPASITAS ANGGARAN DAERAH TERHADAP KASUS COVID 19: STUDI PADA PEMERINTAH DAERAH DI KALIMANTAN BARAT - Indriani, Ika Kurnia; Widodo, Agus; Rukmi, Murti Puspita (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
The covid 19 pandemic has had a major impact on regional economic conditions. The assessment of the financial condition of the regional government is one way to see the effect of budget capacity on the case of covid 19. The financial condition of the regional government will be seen from the high dimensional index value. This study aims to analyze the effect of budget capacity on cases of covid 19 and obtain a dimensional index of financial condition as an indicator of the region's ability to deal with the covid 19 pandemic. The results show that budget capacity of local government have simultaneous effect on covid 19 cases with sig. 0,001. PAD sig. 0,001, DAK sig 0,001, and regional capital expenditures sig. 0,012 have an partial effect on cases of covid 19 . The financial condition of the regional government in West Kalimantan in good condition. This is illustrated by the best service solvency index being Sekadau, Ketapang, Landak, and Pontianak, the best financial independence dimension index is Pontianak, the best service solvency dimension index is Kayong Utara and Kapuas Hulu.